1992
DOI: 10.1159/000126186
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Injections of L-Glutamic Acid, in Contrast to Those of N-Methyl-D,L-Aspartic Acid, Fail to Elicit Sustained Hypothalamic GnRH Release in the Prepubertal Male Rhesus Monkey (Macaca mulatta)

Abstract: The purpose of the present study was to examine whether repetitive intravenous injections of L-glutamic acid (Glu), like those of N-methyl-D, L-aspartic acid (NMA), are able to elicit a sustained train of gonadotropin releasing hormone (GnRH) discharges from the hypothalamus of the prepubertal male monkey. In order to utilize pituitary luteinizing hormone (LH) secretion as a bioassay of hypothalamic GnRH release, the responsiveness of the gonadotroph of the prepubertal animals was enhanced prior to the study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…administration of NMA was markedly attenuated in chronically orchidectomized monkeys as compared with intact animals, although no large differences were observed between the mean basal plasma GH concentrations of agonadal and intact animals. The inability of NMA to stimulate a significant increase in GH secretion in orchidectomized adult monkeys is contrary to earlier reports that demonstrated that NMA can elicit a significant increase in GH secretion in orchidectomized prepubertal monkeys (Plant et al 1989, Medhamurthy et al 1992 and in some other mammalian species (Estienne et al 1989, Barb et al 1992.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…administration of NMA was markedly attenuated in chronically orchidectomized monkeys as compared with intact animals, although no large differences were observed between the mean basal plasma GH concentrations of agonadal and intact animals. The inability of NMA to stimulate a significant increase in GH secretion in orchidectomized adult monkeys is contrary to earlier reports that demonstrated that NMA can elicit a significant increase in GH secretion in orchidectomized prepubertal monkeys (Plant et al 1989, Medhamurthy et al 1992 and in some other mammalian species (Estienne et al 1989, Barb et al 1992.…”
Section: Discussionmentioning
confidence: 64%
“…administration of the neuroexcitatory amino acid agonist NMA induced a prompt discharge of GH in adult intact male monkeys is not surprising. The ability of NMA to evoke a release of GH has been well documented for rats (Mason et al 1983), pigs (Barb et al 1992), sheep (Estienne et al 1989), holstein bulls (Shahab et al 1993) and monkeys (Plant et al 1989, Medhamurthy et al 1992. The excitatory effects of NMA on GH secretion have been shown to be exerted via the discharge of GHRH from the hypothalamus (Cocilovo et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the dose of kainate and AMPA necessary for LH release (1-2.5 mg/kg BW) are considerably less than those required for NMDA. Interestingly, NMDA has been shown to be able to repeatedly stimulate LH release when administered in a pulsatile manner [60,77], In contrast, kainate failed to stimulate LH release in a repetitive manner since the first kainate injection elevated LH release but subsequent injections did not [60,77], Whether AMPA repetitively stimulates LH release has not been determined.…”
Section: Effect Oj Eaas On Lh Secretionmentioning
confidence: 99%
“…Our in vitro studies indicate that estradiol increased the pulsatile GnRH secretion through a mechanism involving the ERα subtype and the kainate receptor. Although the implication of the glutamatergic system in triggering the onset of puberty is well known, only the NMDA receptor subtype has been involved in this process in vivo in the monkey (60) and in vitro in the rat (61). The participation of the kainate receptor in the estradiol-induced advancement of puberty is interesting and leads to the hypothesis that, during development, as the gonads increase their hormonal secretion, the kainate receptors get activated and are responsible for the estradiol-mediated activation of the GnRH system.…”
Section: Sex Steroid Interaction With Glutamate Receptor-mediated Relmentioning
confidence: 99%